A Phytochrome B-Independent Pathway Restricts Growth at High Levels of Jasmonate Defense. Issue 2 (3rd April 2020) - Major, Ian T.; Guo, Qiang; Zhai, Jinling; Kapali, George; Kramer, David M.; Howe, Gregg A.
Abstract : A phytochrome B-independent pathway restricts growth at high levels of defense, and this growth inhibition is correlated with dysregulation of tryptophan biosynthesis. Abstract: The plant hormone jasmonate (JA) promotes resistance to biotic stress by stimulating the degradation of JASMONATE ZIM-DOMAIN (JAZ) proteins, which relieves repression on MYC transcription factors that execute defense programs. JA-triggered depletion of JAZ proteins in Arabidopsis ( Arabidopsis thaliana ) is also associated with reduced growth and seed production, but the mechanisms underlying these pleiotropic growth effects remain unclear. Here, we investigated this question using an Arabidopsis JAZ-deficient mutant ( jazD ; jaz1–jaz7, jaz9, jaz10, and jaz 13 ) that exhibits high levels of defense and strong growth inhibition. Genetic suppressor screens for mutations that uncouple growth-defense tradeoffs in the jazD mutant identified nine independent causal mutations in the red-light receptor phytochrome B (phyB). Unlike the ability of the phyB mutations to completely uncouple the mild growth-defense phenotypes in a jaz mutant ( jazQ ) defective in JAZ1, JAZ3, JAZ4, JAZ9, and JAZ10, phyB null alleles only weakly alleviated the growth and reproductive defects in the jazD mutant. phyB-independent growth restriction of the jazD mutant was tightly correlated with upregulation of the Trp biosynthetic pathway but not with changes in central carbon metabolism. Interestingly, jazD and jazD phyB plants were insensitive to a chemical inhibitor of Trp biosynthesis, which is a phenotype previously observed in plants expressing hyperactive MYC transcription factors that cannot bind JAZ repressors. These data provide evidence that the mechanisms underlying JA-mediated growth-defense balance depend on the level of defense, and they further establish an association between growth inhibition at high levels of defense and dysregulation of Trp biosynthesis.